Comparative Study on the Application of Mesenchymal Stromal Cells Combined with Tricalcium Phosphate Scaffold into Femoral Bone Defects. Issue 10 (October 2018) - Šponer, Pavel; Kučera, Tomáš; Brtková, Jindra; Urban, Karel; Kočí, Zuzana; Měřička, Pavel; Bezrouk, Aleš; Konrádová, Šimona; Filipová, Alžběta; Filip, Stanislav
This prospective study sought to evaluate the healing quality of implanted ultraporous β-tricalcium phosphate sown with expanded autologous mesenchymal stromal cells (MSCs) into femoral defects during revision hip arthroplasty. A total of 37 osseous defects in 37 patients were treated and evaluated concerning bone regeneration. Nineteen subjects received β-tricalcium phosphate graft material serving as a carrier of expanded autologous MSCs (the trial group A), nine subjects received β-tricalcium phosphate graft material only (the study group B) and nine subjects received cancellous allografts only (the control group C). Clinical and radiographic evaluations were scheduled at 6 weeks, 3, 6, and 12 months post-operatively, and performed at the most recent visit as well. All observed complications were recorded during follow-up to assess the use of an ultraporous β-tricalcium phosphate synthetic graft material combined with expanded MSCs in bone defect repair. The resulting data from participants with accomplished follow-up were processed and statistically evaluated with a Freeman–Halton modification of the Fischer's exact test, a P < 0.05 value was considered to be significant. Whereas no significant difference was observed between the trial group A with β-tricalcium phosphate synthetic graft material serving as a carrier of expanded autologous MSCs and control group C with cancellous impaction allografting in terms of the bone defect healing, significant differences were documented between the study group B with β-tricalcium phosphate graft material only and control group C. Regarding adverse effects, six serious events were recorded during the clinical trial with no causal relationship to the cell product. β-tricalcium phosphate synthetic graft material serving as a carrier of expanded autologous MSCs appears safe and promotes the healing of bone defects in a jeopardized and/or impaired microenvironment. This clinical trial was registered at the EU Clinical Trials Register before patient recruitment (Registration number: EudraCT number 2012-005599-33; Date of registration: 2013-02-04).